Recognition of siRNA asymmetry by TAR RNA binding protein (TRBP) - Gredell, Joseph A. (2010)
The recognition of small interfering RNAs (siRNAs) by the RNA induced silencing complex (RISC) and its precursor, the RISC loading complex (RLC), is a key step in the RNA interference pathway that controls the subsequent sequence-specific mRNA degradation. In Drosophila, selection of the guide strand has been shown to be mediated by the RLC protein R2D2, which senses the relative hybridization stability between the two ends of the siRNA. A protein with similar function has yet to be conclusively identified in humans. We show here that human TAR RNA binding protein (TRBP) alone can bind siRNAs in vitro and sense their asymmetry. We also show that TRBP can bind 21 nucleotide single-stranded RNAs, though with far lower affinity than for double-stranded siRNA, and that TRBP crosslinks preferentially to the 3′ ends of the guide strands of siRNAs. This suggests that TRBP binding depends both on the sequences of the siRNA strands as well as the relative hybridization stability of the ends of the duplex. Together these results demonstrate the importance of the siRNA-TRBP interaction in the selection of the siRNA guide strand in RNAi.